Communist trade in oil and gas : an evaluation of the future export capability of the Soviet bloc - Ebel, Robert E. (New York : Praeger, 1970)
This illustrates the methodology employed by the author in evaluating the export capability of the Soviet bloc without necessarily having to resort to a painstaking analysis of each and every detail that somehow might influence export levels.
Includes bibliographical footnotes.
osa 24/01/2019
Loans
Keywords: Petroleum industry and trade; Natural gas